PENERAPAN PROGRAM REDROSE (REDIFINE OPTEMIZING SERVICE) SEBAGAI INOVASI DALAM PELAYANAN PERTANAHAN DI KECAMATAN RUMBAI KOTA PEKANBARU - Sudaryanto, Sudaryanto; Dailiati, Surya (Jurnal Ilmu Administrasi Negara, 2022)
The land problem that occurs in the city of Pekanbaru, especially the sub-district of Rumbai in the application of redrose is that the community has not been able to access and obtain information and the lack of socialization. Basuki (2013:179) reveals that the attributes of public service innovation are relative advantage, compatibility, complexity, triability and observability. Based on the results of the research that has been carried out, the results show that the redrose program already has advantages that can facilitate land services. The redrose program can reduce existing land problems. Then the redrose program can make it easier to speed up land services in the rumbai sub-district. This program is not yet known by the community as a whole.